Cybercrime and the Council of Europe Budapest Convention: prevention, criminalization, and International Cooperation - Campina, Ana (2022)
The Budapest Convention on Cybercrime (2001) and their Additional Protocols (2021) is considered as one coherent international agreement and the base to prevent, combat and criminalize this dangerous crime. The International Law and the national legislations are being developed according to this Convention, based on the strategic (re)action to this crime that is increasing with the worst consequences all around the world. The Rule of Law were obliged to develop their legislation, mainly Penal Law, considering the emergent need to answer to the most serious violations of the fundamental and the Human rights of their citizens, using the most modern technology through the internet, with capacity and efficacy that seriously affect all dimensions of life. The Budapest Convention on Cybercrime provides the criminalization of conduct; the procedural powers to the criminal investigation; and the International Cooperation as one of the most efficient and law enforcement to prevent and combat the Cybercrime. The 77 States Participants close working with the States Observers, within the International Cooperation strategy, connected with Governments, police authorities (national and international), International Organizations and Institutions have been the more profitable strategic (re)action, promoting the cooperation position to the emerging challenges, although the cybercrime is one of the hardest crimes to face. So, there is an evolution in the instruments and strategies to prevent and combat the Cybercrime, but there is an urgent need of an effective legal and social (re)solution, otherwise there will have world and human irreversible impacts. Finally, from the law and cybercrime challenges, the strategy is largely confirmed by the cooperation: the sharing a) information within the legal frameworks; b) the response – operational or tactical; c) the works in the Darkweb; the market, financial and economic movements facing the cybercrime or to denounce the cybercriminals; d) transparency to prevent the cybercrime evolution and implementation.